Effect Of Transformational Leadership And Organizational Support On Organizational Innovation Among Omani It Smes: The Mediating Role Of Employee Creativity - Humayid, Al-aamri Mohammed Hamad (2022)
The focus of this research is on the relationship between perceived organizational support, transformational leadership, employee creativity, and organizational innovation of small and medium enterprises (SMEs) in the Omani IT sector. Drawing on the resource-based view, this research aims to understand the direct relationship between perceived organizational support and transformational leadership, employee creativity, and organizational innovation. Subsequently, it is also pertinent to investigate the impact of transformational leadership on employee creativity and organizational innovation. As such, the intent of this study is to examine the connection between employee creativity and organizational innovation. Furthermore, this research investigates the mediating effect of employee creativity between perceived organizational support, transformational leadership, and organizational innovation. In addition, it examines the mediating impact of transformational leadership on the relationship between perceived organizational support and organizational innovation as well as its relationship with employee creativity. Moreover, this study was designed as a quantitative study and data was collected at one point in time.